DAMPAK FAKTOR PENGAWASAN DAN KOMPENSASI TERHADAP PENINGKATAN KINERJA PEGAWAI KANTOR SATUAN POLISI PAMONG PRAJA DAN WILAYATUL HISBAH KOTA BANDA ACEH - Amelia, Kiki Putri; Havizatun, Melvi (Jurnal Bisnis Digital, 2021)
This study aims to examine and analyze the effect of supervision of the leadership, compensation, discipline, motivation and performance of the officials of the Civil Service Police Unit and the Wilayatul Hisbah (SATPOL PP WH) Banda Aceh City. The population in this study were all employees of SATPOL PP WH Office Banda Aceh City, amounting to 204 employees. Because the population is relatively limited, the sampling is done by using the census method or the taking of all employees at the SATPOL PP WH Office of Kota Banda Aceh as the research sample. Data analysis technique used in this research is The Structural Equation Modeling (SEM) of statistical software package AMOS 22.0 for hypothesis testing. Proof of Hypothesis is done by using indicator of CR and P value. Because of 4 (four) verificatif hypothesis which tested in this research have CR value above 1,96 or P value smaller than 0,05, then all hypothesis tested reject Ho and accept H1. In other words, supervision of the leadership and compensation has the effect to improve employee performance as long as the independent variable can be improved by the management of SATPOL PP WH Office of Banda Aceh City. The intervening variable that is motivation and discipline has no influence to increase the dependent variable with other words meaning that the improvement of employee performance will be better done by increasing the supervision of the leader and the compensation directly without involving the motivation and discipline variable.